2023
DOI: 10.1002/adma.202210562
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Induced Ferroelectricity in Antiferroelectric Oxide Membranes

Abstract: Despite extensive studies on size effects in ferroelectrics, how structures and properties evolve in antiferroelectrics with reduced dimensions still remains elusive. Given the enormous potential of utilizing antiferroelectrics for high‐energy‐density storage applications, understanding their size effects will provide key information for optimizing device performances at small scales. Here, the fundamental intrinsic size dependence of antiferroelectricity in lead‐free NaNbO3 membranes is investigated. Via a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…These data imply that the SHG intensity along the X direction is presumably driven by a dominant susceptibility tensor element, while the intensity along the Y direction is driven by several susceptibility tensor elements of comparable magnitude. The full SHG tensorial analysis of these polar plots would provide the local orientation of the crystallographic axes at the single NW level and possibly reveal the local defects with distinct crystallographic orientations or the presence of AFE domains. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data imply that the SHG intensity along the X direction is presumably driven by a dominant susceptibility tensor element, while the intensity along the Y direction is driven by several susceptibility tensor elements of comparable magnitude. The full SHG tensorial analysis of these polar plots would provide the local orientation of the crystallographic axes at the single NW level and possibly reveal the local defects with distinct crystallographic orientations or the presence of AFE domains. , …”
Section: Resultsmentioning
confidence: 99%
“…The full SHG tensorial analysis of these polar plots would provide the local orientation of the crystallographic axes at the single NW level and possibly reveal the local defects with distinct crystallographic orientations or the presence of AFE domains. 51,52 ■…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that P r of PZO films exhibits an increasing trend as the film thickness decreases, suggesting the coexistence of a metastable FE phase when the film is thin (<100 nm) ( 42 44 ). Thus, to mitigate the impact of the FE component we epitaxially grew high-quality PZO films with different thicknesses on SrRuO 3 (SRO) buffered SrTiO 3 (STO) substrates.…”
Section: Strategies To Improve Switching Ratiomentioning
confidence: 99%
“…On the other hand, from the perspective of symmetry, ferroelectricity must destroy spatial inversion symmetry, while ferromagnetism must destroy temporal inversion symmetry [54]. Therefore, magnetoelectric polyferism requires the inversion symmetry of time and space to be broken [55].…”
Section: Challengesmentioning
confidence: 99%